God and the creative imagination : metaphor, symbol, and myth in religion and theology - Avis, Paul D. L. (Routledge, 1999)
In God and the Creative Imagination, Paul Avis argues that metaphor, symbol and myth, are the key to a real knowledge of God and the sacred.